FACTORS AFFECTING QUALITY OF LIFE AND LEVEL OF SOCIAL SUPPORT IN CANCER PATIENTS - Ayse Berivan Bakan; Asuman Guraksin (Belitung Raya Foundation, Indonesia, 2017)
Background: When people face health problems, their life satisfaction levels and social relations could be ruined. When it comes to an eerie, deadly and chronic disease like cancer, the individual is much more likely to be affected by it. Objective: This descriptive study aims to identify quality of life and level of social support and the affecting factors in cancer patients. Methods: The sample included 170 patients who applied to internal diseases, radiation oncology, thorax diseases clinics and chemotherapy polyclinic in a university hospital in Turkey between March and August, 2005, who met the research criteria, and who volunteered to participate in the study. The sample represented 20 % of the target population. Data were collected through SF-36 Quality of Life Scale and Multidimensional Scale of perceived social support. Results: The patients’ global quality of life mean score was found 38.67 ± 13.64, and mean score for the perceived social support was found 59.19 ± 17.5. Global quality of life score was higher in those who underwent an operation and who received ambulatory health care. Although global quality of life was not influenced by the gender variable, male patients’ level of well-being was found to be higher. Perceived social support total score was found to be higher in those who knew about their disease. Family support was found to be higher in those who were married and who lived in town; it was found to be low in those who had low socio-economic level and who received inpatient treatment. Friend support was found to be high in those who knew about their disease. Conclusion: There was a linear relationship between perceived social support and quality of life. It is recommended that more studies with wider groups of participants would shed more light to the issue of identifying quality of life, social support level and the relationships between them in cancer patients.